Method for manufacturing multi-level gloss ceramic tiles

CN118684429BActive Publication Date: 2026-10-27MONALISA GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310283113.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-21
Publication Date
2026-10-27
Estimated Expiration
2043-03-21

AI Technical Summary

Technical Problem

然而,这种甜蜜陶瓷砖表面质感比较粗糙,呈现凹凸起伏的效果,光泽度高,具有易藏污的缺点

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118684429B_ABST
    Figure CN118684429B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing multi-layer glossiness ceramic tiles. The method comprises the following steps: sequentially applying a surface glaze and an inkjet printing pattern on a green tile surface; applying a bright dry particle glaze on the green tile surface after the inkjet printing pattern; the raw material composition of the base glaze of the bright dry particle glaze comprises, in percentage by mass, 80-92% of dry particles and 8-20% of antique glaze; the chemical composition of the dry particles comprises, in percentage by mass, 56-68% of SiO2, 9-18% of Al2O3, 10-18% of alkaline earth metal oxide, 5-9% of alkali metal oxide and 1-4% of ZnO; the chemical composition of the antique glaze comprises, in percentage by mass, 48-50% of SiO2, 22-24% of Al2O3, 8-15% of alkaline earth metal oxide, 4-8% of alkali metal oxide, 0.8-2.5% of ZnO and 6-9% of loss on ignition; and the green tile after the bright dry particle glaze is fired and polished to obtain the multi-layer glossiness ceramic tile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing multi-layered gloss ceramic tiles, belonging to the field of ceramic tile decoration technology. Background Technology

[0002] With rising living standards, people have increasingly diversified requirements for ceramic tile decoration. Taking this opportunity, dry-granule glaze products have gradually entered the market. Dry-granule glaze possesses characteristics such as non-sedimentation, non-agglomeration, uniform dispersion, and strong adhesion. It also exhibits strong compatibility with inkjet printing inks, offering advantages such as non-repulsion, short drying time, and good breathability. Currently, dry-granule glaze ceramic tiles have become a hot product in the ceramic industry's production and research and development. Ceramic tiles decorated with dry-granule glaze have uniformly dispersed dry granules on the surface, free from defects such as pinholes, glaze bubbles, and glaze bursting, resulting in clear and richly layered decorative patterns. However, most dry-granule glaze ceramic tile products on the market exhibit a single gloss level.

[0003] Chinese patent CN105218158B discloses a type of "sweet ceramic tile" which involves applying a surface glaze to the ceramic tile body, followed by the application of dry granules, and then firing and post-processing to obtain the sweet ceramic tile. The surface of this tile has a uniform distribution of dry granules, giving it a texture and three-dimensional feel reminiscent of granulated sugar. However, this type of sweet ceramic tile has a relatively rough surface texture, exhibiting an uneven effect, and while it has a high gloss, it is prone to accumulating dirt. Summary of the Invention

[0004] This invention is achieved through the following technical solution:

[0005] The method for preparing multi-layered gloss ceramic tiles according to the present invention includes the following steps: Apply a glaze and then print a pattern using inkjet printing on the surface of the brick blank. A glossy dry-granule glaze is applied to the surface of the brick blank after inkjet printing the pattern. The raw material composition of the base glaze of the glossy dry-granule glaze includes: by mass percentage, 80-92% dry granules and 8-20% antique glaze; the chemical composition of the dry granules includes: by mass percentage, SiO2: 56-68%, Al2O3: 9-18%, alkaline earth metal oxides: 10-18%, alkali metal oxides: 5-9%, ZnO: 1-4%; the chemical composition of the antique glaze includes: by mass percentage, SiO2: 48-50%, Al2O3: 22-24%, alkaline earth metal oxides: 8-15%, alkali metal oxides: 4-8%, ZnO: 0.8-2.5%, loss on ignition: 6-9%. After applying a glossy dry granule glaze, the brick blank is fired and polished to obtain ceramic tiles with multi-layered gloss.

[0006] Preferably, the initial melting temperature of the dry granules is 890–920°C; more preferably, the chemical composition of the dry granules includes, by mass percentage: loss on ignition: 0.2–1.1%, SiO2: 56–68%, Al2O3: 9–18%, Fe2O3: 0.1–0.5%, CaO: 10–12%, MgO: 0.6–2.5%, K2O: 0.8–1.4%, Na2O: 4.5–6.5%, P2O5: 0.2–0.4%, ZnO: 1–4%.

[0007] Preferably, the particle size of the dry granules is 120–250 mesh.

[0008] Preferably, the initial melting temperature of the antique glaze is 870–900℃; more preferably, the chemical composition of the antique glaze includes, by mass percentage: loss on ignition: 6–9%, SiO2: 48–50%, Al2O3: 22–24%, Fe2O3: 0.18–0.28%, TiO2: 0.1–0.2%, CaO: 5–8%, MgO: 2–4%, K2O: 0.5–1.5%, Na2O: 4–6%, P2O5: 0.2–0.4%, ZnO: 0.8–2.5%, BaO: 1–3%.

[0009] Ideally, the initial melting temperature of the antique glaze should be 15–25°C lower than that of the dry granules.

[0010] Preferably, the glossy dry-granule glaze is applied by pouring; its specific gravity is 1.20–1.25 g / cm³. 3 The glaze application amount is 240-260 g / m². 2 .

[0011] Preferably, the chemical composition of the glaze includes, by mass percentage: SiO2: 49-58%, Al2O3: 20-31%, alkaline earth metal oxides: 0.2-2%, alkali metal oxides: 7-10%, ZrO2: 5-7%; more preferably, the chemical composition of the glaze includes, by mass percentage: loss on ignition: 4.0-5.0%, SiO2: 49-58%, Al2O3: 20-31%, Fe2O3: 0.2-0.5%, TiO2: 0.05-0.07%, CaO: 0.1-0.9%, MgO: 0.1-0.4%, K2O: 4.8-5.7%, Na2O: 2.5-3.5%, P2O5: 0.2-0.5%, ZrO2: 5-6.5%.

[0012] Preferably, the glaze is applied by spraying; the specific gravity is 1.42–1.46 g / cm³. 3 The glaze application amount is 580-600 g / m². 2 .

[0013] Preferably, the maximum firing temperature is 1187–1223℃, and the firing cycle is 50–55 minutes.

[0014] Preferably, after polishing, the gloss of the raised parts of the multi-layered gloss ceramic tile is 5 to 10 degrees, and the gloss of the relatively concave parts around the raised parts is 90 to 100 degrees. Attached Figure Description

[0015] Figure 1 This is a picture of the brick surface before polishing in Example 1.

[0016] Figure 2 This is a picture of the polished brick surface after Example 1.

[0017] Figure 3 This is a comparison image of the brick surface before polishing, shown in Example 2. Detailed Implementation

[0018] The present invention is further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention. Unless otherwise specified, all percentage contents refer to mass percentages. The following exemplarily illustrates a method for preparing multi-layered gloss ceramic tiles.

[0019] The brick blanks are formed from the green body powder. Dry pressing can be used to obtain the brick blanks. The composition of the green body powder is not limited; conventional green body powders in this field can be used. For example, the chemical composition of the green body powder includes, by mass percentage: SiO2: 60–70%, Al2O3: 19–25%, Fe2O3: 0.5–1.5%, TiO2: 0.2–0.5%, CaO: 0.2–0.8%, MgO: 0.3–0.8%, K2O: 2.0–4.0%, Na2O: 1.5–3.5%, and loss on ignition: 4.0–6.0%.

[0020] Dry the brick blanks. The drying time can be 1 to 1.5 hours. The drying temperature can be 150 to 200℃. The moisture content of the dried brick blanks should be controlled below 0.5 wt%.

[0021] A surface glaze is applied to the dried brick blank. The surface glaze can cover surface defects of the brick blank and enhance the color performance of the inkjet pattern.

[0022] The chemical composition of the glaze includes, by mass percentage: SiO2: 49-58%, Al2O3: 20-31%, alkaline earth metal oxides: 0.2-2%, alkali metal oxides: 7-10%, ZrO2: 5-7%. Preferably, the chemical composition of the glaze includes, by mass percentage: loss on ignition: 4.0-5.0%, SiO2: 49-58%, Al2O3: 20-31%, Fe2O3: 0.2-0.5%, TiO2: 0.05-0.07%, CaO: 0.1-0.9%, MgO: 0.1-0.4%, K2O: 4.8-5.7%, Na2O: 2.5-3.5%, P2O5: 0.2-0.5%, ZrO2: 5-6.5%.

[0023] As an example, the raw material composition of the glaze may include, by mass percentage: albite: 40-50%, calcite: 12-16%, calcined talc: 10-20%, alumina: 1-5%, calcined kaolin: 2-10%, zirconium silicate: 5-15%. In some technical solutions, the raw material composition of the glaze may include, by mass percentage: albite: 49%, calcite: 15%, calcined talc: 15%, alumina: 3%, calcined kaolin: 8%, zirconium silicate: 10%. Weigh each raw material according to the above raw material composition of the glaze, add water, ball mill, and sieve to obtain the glaze slurry.

[0024] The surface glaze can be applied by spraying. For example, the specific gravity of the surface glaze can be 1.42–1.46 g / cm³. 3 The glaze application rate can be 580–600 g / m². 2 Compared to spray-on glaze, spray-on glaze creates a textured surface, enhancing the texture of the subsequent glossy dry-granule glaze. Furthermore, the glazing process allows for better control of the moisture content introduced into the glaze, preventing the spread of oil-based inks during inkjet printing and reducing pattern clarity. It also creates a glaze layer of sufficient thickness to cover the base color of the tile and promote inkjet printing color development.

[0025] The pattern is printed using inkjet printing on the surface of the brick after the glaze has been applied. The color and pattern of the inkjet printed pattern vary according to the layout design.

[0026] A glossy dry-granule glaze is applied to the surface of the brick after inkjet printing the pattern. The base glaze of the glossy dry-granule glaze consists of 80-92% dry granules and 8-20% antique glaze by weight. The percentage of dry granules must be significantly higher than that of antique glaze to enhance the texture of the glossy dry-granule glaze. Conversely, if the antique glaze content is too high, the dry granules will be sparsely distributed, resulting in a poor three-dimensional effect on the glaze surface. Polishing will damage the high-gloss glaze in recessed areas, making it difficult to achieve a layered gloss. If the antique glaze is omitted, the brick surface will have poor stain resistance after firing. Furthermore, the glossy dry-granule glaze uses a lower antique glaze content primarily to reduce glaze porosity and improve stain resistance, without reducing the gloss of recessed areas.

[0027] The chemical composition of the dry granules includes, by mass percentage: SiO2: 56-68%, Al2O3: 9-18%, alkaline earth metal oxides: 10-18%, alkali metal oxides: 5-9%, ZnO: 1-4%. Preferably, the chemical composition of the dry granules includes, by mass percentage: loss on ignition: 0.2-1.1%, SiO2: 56-68%, Al2O3: 9-18%, Fe2O3: 0.1-0.5%, CaO: 10-12%, MgO: 0.6-2.5%, K2O: 0.8-1.4%, Na2O: 4.5-6.5%, P2O5: 0.2-0.4%, ZnO: 1-4%.

[0028] The initial melting temperature of the aforementioned dry granules is 890–920℃. If the initial melting temperature of the dry granules is too high, the melting properties are poor, and it is difficult to cover the depressions around the raised areas with a high-gloss dry granule glaze. If the initial melting temperature of the dry granules is too low, it will lead to over-melting, resulting in a poor raised effect. In addition to contacting the raised areas, the polishing block will also contact the surrounding depressions, thus reducing the gloss of the depressions. This is also not conducive to the formation of multi-layered gloss.

[0029] The raw material composition of the dry granules may include, by mass percentage: albite: 32-35%, calcite: 6-10%, calcined talc: 6-8%, alumina: 8-12%, calcined kaolin: 8-10%, quartz: 25-28%, and zinc oxide: 2-4%. Quartz is introduced to enhance the gloss of the dry granules, while alumina and calcined kaolin are introduced to maintain the three-dimensional appearance of the dry granules. In a specific embodiment, the raw material composition of the dry granules may include, by mass percentage: albite: 35%, calcite: 10%, calcined talc: 6%, alumina: 9%, calcined kaolin: 10%, quartz: 26%, and zinc oxide: 4%.

[0030] Preparation of dry granules. Weigh each raw material according to the above-mentioned raw material composition of dry granules, mix them evenly, melt them at 1450-1500℃ for 1-1.2 hours, quench the glass melt obtained after melting, crush it, and sieve it to obtain dry granules.

[0031] The particle size of the dry granules is 120-250 mesh. If the particle size is too small, it is difficult to create a superior textured surface, which is detrimental to achieving a layered gloss. If the particle size is too large, the suspension of the glossy dry granule glaze is poor, which not only degrades production stability but also results in a poor surface texture of the fired ceramic tiles.

[0032] The chemical composition of the antique glaze includes, by mass percentage: SiO2: 48-50%, Al2O3: 22-24%, alkaline earth metal oxides: 8-15%, alkali metal oxides: 4-8%, ZnO: 0.8-2.5%, and loss on ignition: 6-9%. Preferably, the chemical composition of the antique glaze includes, by mass percentage: loss on ignition: 6-9%, SiO2: 48-50%, Al2O3: 22-24%, Fe2O3: 0.18-0.28%, TiO2: 0.1-0.2%, CaO: 5-8%, MgO: 2-4%, K2O: 0.5-1.5%, Na2O: 4-6%, P2O5: 0.2-0.4%, ZnO: 0.8-2.5%, and BaO: 1-3%. The antique glaze can promote the fusion of dry particles, reduce glaze porosity, and improve the anti-fouling performance of the glaze surface.

[0033] The raw material composition of the antique glaze may include, by mass percentage: albite: 52-58%, calcite: 14-18%, calcined talc: 3-5%, alumina: 3-6%, calcined kaolin: 8-12%, barium carbonate: 3-5%, and zinc oxide: 3-5%. In a specific embodiment, the raw material composition of the antique glaze includes, by mass percentage: albite: 56%, calcite: 17%, calcined talc: 5%, alumina: 3%, calcined kaolin: 9%, barium carbonate: 5%, and zinc oxide: 5%.

[0034] The initial melting temperature of the antique glaze is 870–900℃. Preferably, the initial melting temperature of the antique glaze is 15–25℃ lower than that of the dry granules. If the difference in initial melting temperature between the antique glaze and the dry granules exceeds the above range, the antique glaze will prematurely seal the glaze layer, preventing gas from escaping and forming underglaze bubbles; or it may break through the glaze layer to form open cavities, which is not conducive to stain prevention.

[0035] A glaze slurry for preparing a glossy dry-granule glaze is prepared. Dry granules and antique glaze are weighed, and an adhesive is added and mixed thoroughly to obtain the glossy dry-granule glaze slurry. The adhesive can be a commonly used glaze additive glue in the art. The amount of adhesive used can be adjusted as needed. The mass of the adhesive can be 250% to 360% of the base glaze of the glossy dry-granule glaze. In some embodiments, the flow rate of the glossy dry-granule glaze is 30 to 33 seconds. The flow rate of the glossy dry-granule glaze is measured using a flow rate cup with a diameter of 3.5 mm.

[0036] The glossy dry granular glaze is applied by pouring. A bell-shaped pouring method can be used. This results in a dry granular glaze layer with a strong granular texture and is beneficial for production. In some embodiments, the specific gravity of the glossy dry granular glaze is 1.20–1.25 g / cm³. 3 The glaze application amount is 240-260 g / m². 2 Applying too much glossy dry granule glaze will cause excessive accumulation of dry granules, resulting in uneven distribution of raised areas on the tile surface after polishing, thus reducing the overall quality of the tile. Applying too little glossy dry granule glaze will cause excessive dispersion of the dry granules, leading to a decrease in the gloss of the recessed areas when the polishing block contacts the raised areas.

[0037] Dry the brick blanks after applying the glossy dry granule glaze. The drying temperature can be 80-100℃. After drying, the moisture content should be controlled below 0.5wt%.

[0038] The dried brick blanks are then fired. The maximum firing temperature can be 1187℃~1223℃, and the firing cycle can be 50~55 minutes. If the firing cycle is too short, it will not be conducive to the melting of dry particles, resulting in uneven gloss.

[0039] Polishing. The specific implementation uses a combination of polishing blocks: 2 sets of 600-grit elastic grinding blocks, 6 sets of 800-grit elastic grinding blocks, and 3 sets of 600-grit brush grinding blocks. The polishing pressure is 1–2 MPa.

[0040] In summary, this invention employs a glossy dry-granule glaze containing both high-temperature glossy dry granules and an antique glaze (low-temperature low-gloss antique glaze). Before polishing, the tile surface exhibits a glossy and delicate texture. After polishing, the tile surface visually displays an undulating texture, providing a soft and delicate glaze effect with excellent stain resistance. Furthermore, the multi-layered gloss ceramic tile exhibits a gloss level of 5-10 on the raised areas after polishing, while the gloss level of the (relatively) recessed areas around the raised areas is 90-100, creating a multi-layered gloss effect. It should be noted that combining low-gloss dry granules and high-gloss glaze cannot create a multi-layered gloss effect because the distribution of low-gloss dry granules in the recessed areas significantly reduces the gloss, thereby decreasing the gloss contrast between the raised and recessed areas after polishing.

[0041] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0042] Example 1 The method for preparing multi-layered gloss ceramic tiles includes the following steps: Step 1. Dry press the green body powder into brick blanks. Step 2. Dry the brick blanks. The drying temperature is 150℃. The drying time is 1.5 hours. The moisture content of the dried brick blanks should be controlled below 0.5 wt%. Step 3. Spray a top coat of glaze onto the dried brick surface. The chemical composition of the glaze includes, by mass percentage: Loss on ignition: 4.2%, SiO2: 56.15%, Al2O3: 25%, Fe2O3: 0.3%, TiO2: 0.07%, CaO: 0.2%, MgO: 0.2%, K2O: 4.9%, Na2O: 2.7%, P2O5: 0.28%, ZrO2: 6%. The specific gravity of the glaze is 1.44 g / cm³. 3 The glaze application amount is 590g / m² 2 . Step 4. Print a pattern on the surface of the brick after the glaze has been sprayed. Step 5. Apply a glossy dry granule glaze to the surface of the brick blank with the inkjet-printed pattern. The base glaze of the glossy dry granule glaze consists of: 92% dry granules and 8% antique glaze by weight percentage. The chemical composition of the dry granules includes: loss on ignition: 0.38%, SiO2: 67.26%, Al2O3: 9.17%, Fe2O3: 0.15%, CaO: 11.6%, MgO: 2.2%, K2O: 1.02%, Na2O: 6.2%, P2O5: 0.27%, ZnO: 1.75%. The chemical composition of the antique-style glaze includes, by mass percentage: Loss on ignition: 6.89%, SiO2: 49.8%, Al2O3: 23.27%, Fe2O3: 0.22%, TiO2: 0.2%, CaO: 6.44%, MgO: 2.6%, K2O: 0.66%, Na2O: 4.93%, P2O5: 0.32%, BaO: 2.62%, ZnO: 2.05%. The specific gravity of the glossy dry granular glaze is 1.23 g / cm³. 3 The flow rate is 30 seconds, and the glaze application rate is 250g / m³. 2 . Step 6. Dry the brick blanks coated with glossy dry granule glaze. The drying temperature is 90℃, and the moisture content of the brick blanks after drying is controlled to be below 0.5wt%. Step 7. Place the dried brick blanks into a roller kiln for low-temperature rapid firing. The maximum firing temperature is 1187℃, and the firing cycle is 55 minutes. Step 8. Polishing, edge grinding, and grading.

[0043] The brick surface has a textured, undulating feel and a soft, delicate touch. Combined with... Figure 1 and Figure 2As can be seen, the overall gloss of the brick surface is high before polishing, while the gloss of the raised parts reaches about 8 degrees after polishing, and the gloss of the recessed parts around the raised parts is about 95 degrees, thus presenting a multi-layered gloss effect.

[0044] Comparative Example 1 It is basically the same as Example 1, except that: In step 5, the raw material composition of the antique glaze includes, by mass percentage: albite: 51%, calcite: 12%, calcined talc: 5%, alumina: 8%, calcined kaolin: 18%, barium carbonate: 3%, and zinc oxide: 3%.

[0045] The comparison uses a high-temperature antique glaze, but this high-temperature antique glaze cannot promote the fusion between dry particles. On the one hand, it will result in poor stain resistance of the glaze surface, and on the other hand, it will reduce the gloss of the glaze surface in the recessed areas, thereby reducing the contrast between the gloss levels.

[0046] Comparative Example 2 It is basically the same as Example 1, except that: Step 5. The raw material composition of the base glaze for the glossy dry granule glaze includes: 92% dry granules and 8% polishing glaze by mass percentage. The raw material composition and chemical composition of the dry granules are basically the same as in Example 1. The raw material composition of the polishing glaze includes: 26% potassium feldspar, 30% sodium feldspar, 7% calcite, 9% calcined talc, 5% alumina, 10% calcined kaolin, 8% barium carbonate, and 5% zinc oxide by mass percentage. The initial melting temperature of the polishing glaze is 780℃. The chemical composition of the polishing glaze includes: 12% loss on ignition, 47% SiO2, 12% Al2O3, 0.25% Fe2O3, 7.1% CaO, 5.5% MgO, 2.8% K2O, 3.1% Na2O, 0.25% P2O5, 6.6% BaO, and 3.4% ZnO by mass percentage.

[0047] This comparative example uses low-temperature polishing. Because the initial melting temperature of low-temperature polishing is much lower than that of dry granules, the dry granules over-melt, therefore... Figure 3 As shown, the dry particles on the brick surface after firing have poor three-dimensionality and it is difficult to form a layered gloss.

[0048] Comparative Example 3 It is basically the same as Example 1, except that: Step 5. The raw material composition of the base glaze for the glossy dry granule glaze includes: 50% dry granules and 50% antique glaze by mass percentage. The raw material composition and chemical composition of the dry granules and the antique glaze are basically the same as those in Example 1.

[0049] In this comparative example, due to the high percentage of the mass of the antique glaze, the dry particles are sparsely distributed, resulting in poor three-dimensionality of the glaze surface. Even the recessed areas around the protrusions are easily touched by the polishing blocks, which reduces the gloss of the recessed areas and is not conducive to the formation of multi-layered gloss.

Claims

1. A method for preparing multi-layered gloss ceramic tiles, characterized in that, Includes the following steps: Apply a glaze and then print a pattern using inkjet printing on the surface of the brick blank. Apply a glossy dry granule glaze to the surface of the brick blank after inkjet printing the pattern; The raw material composition of the base glaze for glossy dry granule glaze includes: by mass percentage, 80-92% dry granules and 8-20% antique glaze; the chemical composition of the dry granules includes: by mass percentage, SiO2: 56-68%, Al2O3: 9-18%, alkaline earth metal oxides: 10-18%, alkali metal oxides: 5-9%, ZnO: 1-4%; the chemical composition of the antique glaze includes: by mass percentage, SiO2: 48-50%, Al2O3: 22-24%, alkaline earth metal oxides: 8-15%, alkali metal oxides: 4-8%, ZnO: 0.8-2.5%, loss on ignition: 6-9%; the initial melting temperature of the antique glaze is 15-25℃ lower than that of the dry granules. After applying a glossy dry granule glaze, the brick blank is fired and polished to obtain ceramic tiles with multi-layered gloss.

2. The method according to claim 1, characterized in that, The initial melting temperature of the dry granules is 890–920℃.

3. The method according to claim 1 or 2, characterized in that, The chemical composition of the dry granules includes, by mass percentage: Loss on ignition: 0.2–1.1%, SiO2: 56–68%, Al2O3: 9–18%, Fe2O3: 0.1–0.5%, CaO: 10–12%, MgO: 0.6–2.5%, K2O: 0.8–1.4%, Na2O: 4.5–6.5%, P2O5: 0.2–0.4%, ZnO: 1–4%.

4. The method according to claim 1, characterized in that, The dry granules have a particle size of 120–250 mesh.

5. The method according to claim 1, characterized in that, The initial melting temperature of antique-style glaze is 870–900℃.

6. The method according to claim 1, characterized in that, The chemical composition of the antique-style glaze includes, by mass percentage: loss on ignition: 6-9%, SiO2: 48-50%, Al2O3: 22-24%, Fe2O3: 0.18-0.28%, TiO2: 0.1-0.2%, CaO: 5-8%, MgO: 2-4%, K2O: 0.5-1.5%, Na2O: 4-6%, P2O5: 0.2-0.4%, ZnO: 0.8-2.5%, BaO: 1-3%.

7. The method according to claim 1, characterized in that, The glossy dry-granule glaze is applied by pouring; its specific gravity is 1.20–1.25 g / cm³. 3 The glaze application rate is 240–260 g / m². 2 .

8. The method according to claim 1, characterized in that, The chemical composition of the glaze includes, by mass percentage: SiO2: 49-58%, Al2O3: 20-31%, alkaline earth metal oxides: 0.2-2%, alkali metal oxides: 7-10%, ZrO2: 5-7%.

9. The method according to claim 8, characterized in that, The chemical composition of the glaze includes, by mass percentage: loss on ignition: 4.0–5.0%, SiO2: 49–58%, Al2O3: 20–31%, Fe2O3: 0.2–0.5%, TiO2: 0.05–0.07%, CaO: 0.1–0.9%, MgO: 0.1–0.4%, K2O: 4.8–5.7%, Na2O: 2.5–3.5%, P2O5: 0.2–0.5%, ZrO2: 5–6.5%.

10. The method according to claim 1, characterized in that, The glaze is applied by spraying; its specific gravity is 1.42–1.46 g / cm³. 3 The glaze application rate is 580–600 g / m². 2 .

11. The method according to claim 1, characterized in that, The maximum firing temperature is 1187–1223℃, and the firing cycle is 50–55 minutes.

12. The method according to claim 1, characterized in that, Multi-layered gloss ceramic tiles have a gloss level of 5-10 degrees on the raised parts after polishing, and a gloss level of 90-100 degrees on the relatively concave parts around the raised parts.

Citation Information

Patent Citations

  • A sweet ceramic tile

    CN105218158B

  • Composite glaze with low glossiness and high pollution resistance, granite porcelain tile using composite glaze and preparation method of granite porcelain tile

    CN112225454A

  • Ceramic rock plate with low-gloss fine frosted effect surface and preparation method of ceramic rock plate

    CN114454303A